1991
DOI: 10.1128/aem.57.11.3193-3199.1991
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobicity, Adhesion, and Surface-Exposed Proteins of Gliding Bacteria

Abstract: The cell surface hydrophobicities of a variety of aquatic and terrestrial gliding bacteria were measured by an assay of bacterial adherence to hydrocarbons (BATH), hydrophobic interaction chromatography, and the salt aggregation test. The bacteria demonstrated a broad range of hydrophobicities. Results among the three hydrophobicity assays performed on very hydrophilic strains were quite consistent. Bacterial adhesion to glass did not correlate with any particular measure of surface hydrophobicity. Several adh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
1

Year Published

1992
1992
2016
2016

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(22 citation statements)
references
References 42 publications
1
18
0
1
Order By: Relevance
“…For Listeria, the optimum metabolic activity and attachment conditions were at 30 ЊC and pH 7, and for Yersinia the optimum was at 21 ЊC and pH 8 to 9. Sorongon (1991) observed that starvation of Cytophaga increases surface hydrophobicity. Other studies have correlated adhesion with surface charge and hydrophobicity.…”
Section: Adhesive Properties Of the Bacterial Cell Surfacementioning
confidence: 99%
“…For Listeria, the optimum metabolic activity and attachment conditions were at 30 ЊC and pH 7, and for Yersinia the optimum was at 21 ЊC and pH 8 to 9. Sorongon (1991) observed that starvation of Cytophaga increases surface hydrophobicity. Other studies have correlated adhesion with surface charge and hydrophobicity.…”
Section: Adhesive Properties Of the Bacterial Cell Surfacementioning
confidence: 99%
“…Hydrophobicity tends to increase with the age of the bacterium, as in the case of Acinetobacter calcoaceticus (Rosenberg et al 1981). Differences between strains of the same species have also been observed, for example in the case of different strains of Cytophaga johnsonae (Sorongon et al 1991) or Vibrio species (Lee and Yii 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The best method to avoid bacterial aggregation with a significant amount of bacterial yields was to inoculate bacteria directly into marine broth at 25°C for 48 h with vigorous shaking. The role of strong agitation in preventing bacterial slime formation and aggregation was already reported by Burchard & Schwarz (1989) and Sorongon, Bloodgood & Burchard (1991). These authors observed that static liquid cultures revealed detectable slimy bacteria manifested by increasing culture viscosity, while during shaking conditions, some of the extracellular polymers constituting the slime were sloughed off and therefore increased bacterial hydrophobicity, which in turn reduces surface bacterial adhesion and biofilm formation.…”
Section: Discussionmentioning
confidence: 63%